A novel locus for autosomal dominant non-syndromic deafness, DFNA53, maps to chromosome 14q11.2-q12. Issue 2 (15th June 2005) - Yan, D; Ke, X; Blanton, S H; Ouyang, X M; Pandya, A; Du, L L; Nance, W E; Liu, X Z
Abstract : Background: Non-syndromic hearing loss is among the most genetically heterogeneous traits known in humans. To date, at least 50 loci for autosomal dominant non-syndromic sensorineural hearing loss (ADNSSHL) have been identified by linkage analysis. Objective: To report the mapping of a novel autosomal dominant deafness locus on the long arm of chromosome 14 at 14q11.2-q12, DFNA53, in a large multigenerational Chinese family with post-lingual, high frequency hearing loss that progresses to involve all frequencies. Results: A maximum multipoint LOD score of 5.4 was obtained for marker D14S1280. The analysis of recombinant haplotypes mapped DFNA53 to a 9.6 cM region interval between markers D14S581 and D14S1021. Four deafness loci (DFNA9, DFNA23, DFNB5, and DFNB35) have previously been mapped to the long arm of chromosome 14. The critical region for DFNA53 contains the gene for DFNA9 but does not overlap with the regions for DFNB5, DFNA23, or DFNB35. Screening of the COCH gene (DFNA9), BOCT, EFS, and HSPC156 within the DFNA53 interval did not identify the cause for deafness in this family. Conclusions: Identifying the DFNA53 locus is the first step in isolating the gene responsible for hearing loss in this large multigeneration Chinese family.